2019
DOI: 10.18203/2319-2003.ijbcp20190658
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Morus alba (Mulberry) leaves extract for anti-convulsant property in rats

Abstract: Background: The mulberry tree, a plant of the family Moraceae and the genus Morus, has been widely cultivated to feed silkworms. Various parts of Morus alba linn used as an Anti-inflammatory, hypoglycemic, cardioprotective, hepatoprotective, free radical scavenging activity and neuroprotective agent. The plant contains flavonoids, moranoline, albanol, morusin coumarine, and stilbene, which have. In this study, anticonvulsant property of Morus alba leaves extract (MAE) was evaluated by using MES and PTZ induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…These concentrations also significantly reduced the maximal electroshock-induced tonic hindlimb extension [ 75 ]. Meanwhile, M. alba leaves’ significant antiepileptic activity at 200 and 400 mg/kg at 6.8 and 3.16 s, respectively, was observed by Rayam et al [ 76 ].…”
Section: Nutraceutical Properties Of Morus Albamentioning
confidence: 92%
See 1 more Smart Citation
“…These concentrations also significantly reduced the maximal electroshock-induced tonic hindlimb extension [ 75 ]. Meanwhile, M. alba leaves’ significant antiepileptic activity at 200 and 400 mg/kg at 6.8 and 3.16 s, respectively, was observed by Rayam et al [ 76 ].…”
Section: Nutraceutical Properties Of Morus Albamentioning
confidence: 92%
“…According to Gupta et al [ 75 ] and Rayam et al [ 76 ], M. alba leaves could facilitate gamma-aminobutyric acid (GABA) transmission, thus exhibiting an anticonvulsant ability in rats [ 77 ]. A 25 mg/kg methanolic leaf extract actually postponed the onset of pentylenetetrazole (PTZ)-induced chronic seizure.…”
Section: Nutraceutical Properties Of Morus Albamentioning
confidence: 99%
“…These concentrations also significantly reduced maximal electroshock-induced tonic hindlimb extension (Gupta et al, 2018). Meanwhile, M. alba leaves significant antiepileptic activity at 200 and 400 mg/kg at 6.8 and 3.16 s, respectively, as reported by (Rayam et al, 2019) was observed. In the context of Alzheimer's disease, 28-day administration of 100 mg/kg ethanolic leaves improved M. alba both learning and memory function in spatially-impaired rats, while the 200 mg/kg and 400-mg/kg mg/kg extracts inhibited the effect on memory disorders (Tamtaji et al, 2016).…”
Section: Neuroactive Abilitymentioning
confidence: 51%
“…According to (Gupta et al, 2018) and (Rayam et al, 2019), M. alba leaves could facilitate the transfer of gamma-aminobutyric acid (GABA) and thus show an antispasmodic effect in rats (Diniz et al, 2015). A 25 mg/kg methanolic leaf extract actually delayed the onset of pentylenetetrazole (PTZ)-induced chronic seizures.…”
Section: Neuroactive Abilitymentioning
confidence: 99%
“…12 M. alba leaves extract showed anticonvulsant effects in MES induced convulsions and in PTZ induced convulsions. 13 A piperidine alkaloid and some glycoproteins were isolated from the bark and leaves, which had antidiabetic effects. 14 Taking this into consideration the reported psychopharmacological effects of morus alba leaves in various animal models, ignited a spirit to evaluate antipsychotic effects of M. alba leaves extract by haloperidol induced catalepsy model in rats.…”
Section: Introductionmentioning
confidence: 99%